ELLIPSOMETRY BASED SPECTROSCOPIC COMPLEX FOR RAPID ASSESSMENT OF THE Bi2Te3-xSex THIN FILMS COMPOSITION - Kovalev, Vladimir; Uvaysov, Saygid; Bogucki, Marcin (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2021)
A comparative analysis of the current state and development of spectral ellipsometry (SE) is carried out, the main limitations typical of popular configurations of measuring devices are determined. An original technical solution is proposed that allows one to create a two-source SE that implements the ellipsometry method with switching orthogonal polarization states. The measuring setup provides high precision of measurements of ellipsometric parameters Ψ and Δ in the spectral range of 270–2200 nm and the speed determined by the characteristics of pulsed sources with a simple ellipsometer design. As objects for experimental researches, confirming the efficiency and high precision qualities of the fabricated SE, we used a GaAs/ZnS-quarter-wave device for a CO2 laser and SiO2 on Si calibration plates. The optical properties of Bi2Te3-xSex films were investigated in the range of 270–1000 nm using a multi-angle SE. It was shown that the optical properties of Bi2Te3-xSex films monotonically change depending on the ratio of selenium and tellurium.